Pengaruh Kecerdasan Emosional dan Kecerdasan Spiritual Terhadap Pemahaman Akuntansi Pada Mahasiswa Jurusan Akuntansi Universitas Swasta di Bali - I Wayan Wahyu Diatmika; I Wayan Rupa; I. B. Made Putra Manuaba (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Warmadewa, 2020)
This research aims to test, emotional intelligence and spiritual intelligence have an effect on the level of understanding accounting. The population in this study were all active students majoring in accounting at private universities in Bali. The research sample was obtained as many as 93 students who were taken using the slovin formula. Data analysis techniques using multiple linear regression analysis. Based on the results of the study, it shows that emotional intelligence and spiritual intelligence have a significant positive effect on the level of accounting understanding, there are significant differences in emotional intelligence, spiritual intelligence and accounting comprehension.